Konstruksi Tafsir al-Qur’anul Majid An-Nur Karya M Hasbi Ash-Shiddieqy - S Sudariyah (SHAHIH: Journal of Islamicate Multidisciplinary, 2018)
This article describes the thoughts of M Hasbi Ash-Shiddieqy in understanding or interpreting the verses of the law. This discussion is descriptive-analytic with a focus on his work of Tafsir al-Qur'anul Majid An-Nur. As for the novelty of this study is the researchers tried to see the construction of Tafsir al-Qur'anul Majid An-Nur, which includes two aspects, namely internal and external. The internal aspects include methods and techniques of interpretation, while the external aspects include the social conditions of society which then affect the Hasbi interpretation model that is very typical with the nuances of Indonesianness, especially in legal matters. The results of this study indicate that in interpreting the verses of Hasbi's law does not necessarily accept the law textually or interpret the verses of the law in accordance with the sect of it, the school of Shafi'i, but he also tried to explain or describe about various history or opinion of the scholars according to the theme, then new Hasbi linked with the context of life of Indonesian society is very pluralistic.